Nursing New Insights for Clinical Care - Chaban, Victor (IntechOpen, 2023)
This book provides comprehensive insights into all aspects of nursing care and research, with an up-to-date assessment of current clinical practices worldwide. Today's nurses play a significant role in clinical settings not only as caregivers, but also as educators and patient advocates helping all types of people from different socioeconomic backgrounds, religious beliefs, and political alignments. With most countries impacted negatively by the Covid-19 pandemic, and significant global health disparities remaining, the concept of "global health" is now well accepted. Nurses and other healthcare providers across the world are doing their best to come up with effective treatments for many diseases, both common and rare, and recognize that it is important to treat not only the physiological and pathological presentations of disease but also patients' emotional needs. The quality of patient care and clinical competences have a powerful impact on therapeutic progression and recovery. This book aims to help healthcare providers and facilities give their patients excellent treatment and experiences, with a team of international experts presenting their best practices in the treatment of different metabolic and psychiatric diseases and conditions. The book is recommended for nurses, healthcare professionals, students and patients who are focused on the care of individuals, families, and communities.